Iron-based composite nanomaterials for eco-friendly photocatalytic hydrogen generation. Issue 11 (1st June 2022) - Jineesh, P.; Hossain, Aslam; Remya, R.; Sebeelamol, J.N.; Manavalan, Rajesh Kumar; Ahmed, Jahangeer; Tamboli, Mohaseen S.; Shibli, S.M.A.
Abstract: This study deals with different proton sources for the enhancement of hydrogen generation by a powder-type complex photocatalytic system. This article reports on the undesirable role of external influences for eco-friendly hydrogen generation using low-cost iron-based nanomaterials. The synthesized material using a metal-organic framework template strategy was confirmed by in-situ characterizations. The bandgap of Fe2 O3 –TiO2 has been tuned by the formation of a Fe3 O4 @Fe2 O3 –TiO2 complex oxide. The hydrogen production rate has been enhanced by tuning pH, different sacrificial reagents and proton donors. The optimized condition along with the addition of 0.1 g of aniline hydrochloride as a proton source, enhanced the hydrogen evolution rate to 2.366 mmol/0.5 g/h which resulted in high quantum efficiency. Methanol played a crucial role as a sacrificial agent along with the addition of aniline hydrochloride as a proton source for this outstanding hydrogen evolution activity, which is explained by proposing a mechanism. The ultra-pure production of hydrogen gas (98.30%), apparent quantum efficiency of almost 74% under sunlight, and reusability of the proposed photocatalyst have been studied in detail. The presence system has many other advantages such as low cost, easy preparation, high stability and nontoxicity. Graphical abstract: Image 1